Relación del gasto público en telecomunicaciones y el porcentaje de la población que accede a internet en Loreto 2011 – 2020 - Torres Soto, Khyra del Chayo (2025)
The research aimed to examine the relationship between public spending on telecommunications and the percentage of the population that accesses the internet in the Loreto region during the period 2011-2020. By analyzing in detail the destination and effectiveness of public funds allocated to the sector, it can be determined which measures are most effective in improving internet access in specific areas and reducing the digital divide. Through a quantitative approach and a correlational design, the annual records of both variables were thoroughly analyzed from 2011 to 2020. The results show that, on average, 25.14% of the population aged 6 and over of the Loreto region accessed the internet service during each of the ten years under analysis. This evidences the need to continue implementing policies and programs that encourage the expansion of telecommunications infrastructure and facilitate Internet access, especially in remote and underserved areas. The inferential analysis revealed that there is no significant relationship, with a 90% confidence level, between public spending on telecommunications and the percentage of the population that accesses the Internet, nor with the item in the functional group of telecommunications services. Otherwise, a positive relationship of 62.33% was found between public spending on market efficiency executed by OSIPTEL and the percentage of the population that accesses the internet in Loreto.